AKIBAT HUKUM PELAKSANAAN KAWIN KONTRAK DITINJAU BERDASARKAN UNDANG-UNDANG PERKAWINAN DAN KUH PERDATA - MUSTAFA, RAHMAWATI (Ganec Swara, 2025)
This study aims to analyze the legal consequences of the implementation of contract marriages in the perspective of the Marriage Law and the Civil Code (KUHPerdata) in Indonesia. Contract marriages, which often occur in society, have various legal implications that need to be understood, especially regarding the validity of the practice. This research uses a normative juridical approach with a descriptive analysis method, which examines the regulation of contract marriages in legislation and its impact on the parties involved. The findings show that contract marriages do not meet the legal requirements of marriage according to the law, so children born from these relationships often do not have a clear legal position, impacting on inheritance rights and recognition status. The research also identifies the lack of legal protection for women in the context of contract marriages, as well as the driving factors behind them, such as economic pressures. Therefore, this research is expected to provide recommendations for better legal arrangements related to marriage in Indonesia and increase public awareness regarding the importance of performing marriage in accordance with applicable legal provisions.